Proclamación de los candidatos de la Liga Loretana - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1919)
SPANISH: En la foto, la directiva de la Liga y los candidatos en el acto de proclamación de las candidatos a la Liga Loretana.
ENGLISH: In the photo, the League's board of directors and the candidates at the ceremony for the proclamation of the candidates for the Loreto League.

SPANISH: En la foto, la directiva de la Liga y los candidatos en el acto de proclamación de las candidatos a la Liga Loretana.
ENGLISH: In the photo, the League's board of directors and the candidates at the ceremony for the proclamation of the candidates for the Loreto League.
Proclamation of the Loretana League candidates
Keywords: Iquitos (Perú)|~|Religious instruction--Catolocism--Institutes (religious), Members of|~|Iquitos Antiguo N°02|~|Iquitos (Perú)|~|Instrucción religiosa|~|Catolicismo|~|Institutos (religiosos), miembros de